Cerdas Digital: Peluang Bisnis di Media Sosial untuk Generasi Z - Meutia, Nur Shabrina; Magfira, Dike Bayu; Ilmi, Zujajatul; Budiarti, Rizqi Putri Nourma (Indonesia Berdaya, 2026)
Abstract. Social media has evolved into one of the most effective platforms for communication, marketing, and business transactions. Generation Z, as digital natives, holds significant potential in leveraging social media as a business platform. However, various challenges remain, ranging from low levels of digital literacy to limited understanding of social media algorithms. This community engagement program was conducted at SMP Insan Cendekia Mandiri Boarding School, Sidoarjo, with the aim of enhancing students’ understanding of digital entrepreneurship, introducing the use of artificial intelligence (AI) for promotion, and training them in creating marketable digital content. The implementation method consisted of four stages: initiation, preparation, execution in the form of socialization and training, and evaluation through pre-tests and post-tests. The results indicated an improvement in students’ comprehension of digital entrepreneurship concepts, their ability to utilize social media productively, and their creativity in content creation. The average pre-test score of 95.14 increased to 96.00 in the post-test, reflecting strengthened conceptual understanding and practical skills. This article underscores the importance of educational strategies and the sustainability of training programs to ensure that young generations can optimize social media as a business tool. Abstrak. Media sosial telah berkembang menjadi salah satu sarana paling efektif untuk komunikasi, pemasaran, sekaligus transaksi bisnis. Generasi Z sebagai generasi digital native memiliki potensi besar dalam memanfaatkan media sosial sebagai platform bisnis. Namun, berbagai tantangan masih dihadapi, mulai dari rendahnya literasi digital hingga pemahaman yang terbatas terkait algoritma media sosial. Kegiatan pengabdian kepada masyarakat ini dilaksanakan di SMP Insan Cendekia Mandiri Boarding School Sidoarjo dengan tujuan meningkatkan pemahaman siswa tentang digital entrepreneurship, memperkenalkan pemanfaatan kecerdasan buatan (AI) untuk promosi, serta melatih keterampilan pembuatan konten digital bernilai jual. Metode pelaksanaan terdiri dari tahap inisiasi, persiapan, eksekusi berupa sosialisasi dan pelatihan, serta evaluasi menggunakan pre-test dan post-test. Hasil menunjukkan adanya peningkatan pemahaman siswa terkait konsep kewirausahaan digital, kemampuan memanfaatkan media sosial secara produktif, serta kreativitas dalam pembuatan konten. Nilai rata-rata pre-test sebesar 95,14 meningkat menjadi 96,00 pada post-test, menunjukkan adanya penguatan pemahaman konseptual dan keterampilan praktis. Artikel ini menegaskan pentingnya strategi edukatif dan keberlanjutan program pelatihan agar generasi muda mampu mengoptimalkan media sosial sebagai sarana bisnis.